2017
DOI: 10.1172/jci.insight.93771
|View full text |Cite
|
Sign up to set email alerts
|

Old age causes de novo intracortical bone remodeling and porosity in mice

Abstract: Reference information: JCI Insight. 2017;2(17):e93771. https://

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
139
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 76 publications
(106 reference statements)
22
139
2
2
Order By: Relevance
“…12D and E). (22) Osteocyte senescence has also been reported by Farr and colleagues. (73) As discussed earlier, MMP13 and SDF1 are likely candidates for the loss of cortical bone caused by estrogen deficiency.…”
Section: The Contribution Of Old Osteocytes To Skeletal Involutionsupporting
confidence: 54%
See 3 more Smart Citations
“…12D and E). (22) Osteocyte senescence has also been reported by Farr and colleagues. (73) As discussed earlier, MMP13 and SDF1 are likely candidates for the loss of cortical bone caused by estrogen deficiency.…”
Section: The Contribution Of Old Osteocytes To Skeletal Involutionsupporting
confidence: 54%
“…Reproduced with permission from Piemontese and colleagues. (22) N.Oc/B.Pm = number of osteoclasts per bone perimeter.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that osteon size positively correlates with body mass in mammals and suggested that the lack of clear osteons in small mammals may be related to the need to avoid fractures (56). Be that as it may, dysregulation of Haversian remodeling, such as may occur with aging, remains difficult to study in rodents (57). …”
Section: Genetic Manipulation Of Animalsmentioning
confidence: 99%